teknologi pendidikan sebagai pembelajaran yang efektif - Saifullah Maysa (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
Not all students obey the rules at school, there are still students who are not disciplined, such as students making chaos in class, disturbing friends, and so on. The application of reward and punishment is one of the strategies for inculcating student discipline. Reward (award) and punishment (punishment) are given as reinforcement and motivation for students in the learning process. To discipline students, students must consider various situations, and understand the factors that influence them, such as studying the experiences of students at school through cumulative note cards, learning the names of students directly, considering the learning environment and student environment, giving clear assignments, understandable, simple and not long-winded, passionate and enthusiastic in doing learning to be used as role models by students, making something different and varied, not monotonous, so as to help discipline and passion for learning students, make clear and firm rules so that can be carried out as well as possible by students and their environment, prepare daily activities so that what is done in learning is according to the plan, there are no many deviations, adjust arguments to the abilities of students, do not force students according to the teacher's understanding know how to measure students from the ability of their teachers, make clear and firm rules so that they can be carried out as well as possible by students and their environment.